The employees of native and immigrant self-employed - Pernilla Andersson; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2007)
Using unique register data for Sweden we can match self-employed persons to their employees. We analyze the national composition of the employees and ask if self-employed immigrants mainly employ workers from their home region and if self-employed natives mainly employ native workers. We find that both natives and immigrants are more likely to employ co-nationals than to employ workers with a different national background. We also analyze which factors influence the propensity to hire co-nationals. For immigrants we find that living in a municipality with a high share of co-nationals decreases the probability of employing natives, while the probability that natives employ immigrants increases with the immigrant share in the municipality. We find that the probability for immigrants to hire native workers increases with time spent in Sweden. This result points to that the proximity to people from the same region and possibly also one's network plays an important role for the employment decisions for both self-employed natives and immigrants.
Keywords: 330; Self-employment; immigrants; networks; Selbstständige; Personalbeschaffung; Migranten; Ethnische Beziehungen; Schweden